Current Situations and Emerging Trends of Artisans’ Capacities in Thailand - Hongrattanavorakit, Sakarin; Suwannarak, Jomkhwun; Peeraphatchara, Chutamas (Journal of Cultural Approach, 2024)
This qualitative study investigated the current state and evolving trends of artisans' capacities in Thai fruit and vegetable carving. Utilizing document analysis and in-depth interviews with eighteen experts, the research employed interview questions as primary data collection tools, further strengthened by data triangulation for comprehensive qualitative analysis. The findings revealed that carving work by artisans in Thailand is primarily organized by both non-formal and formal education systems, structured systematically from foundational basics to advanced patterns; the inheritance of carving careers among Thai artisans spans various sectors including government service, private companies, entrepreneurship, and freelance work; equipment used by carving artisans is classified into main tools and accessories; raw materials encompass Thai and foreign vegetables and fruits; carving patterns range from basic to intermediate and advanced respectively; carving techniques involve knife holding, equipment selection, and proficiency in different carving levels; maintenance practices of Thai carving artisans are categorized into short-term, 1-2 days, and long-term, 3-7 days, strategies; and the benefits of carving work extend beyond artistic expression, serving purposes such as consumption, participation in events, and career opportunities in diverse sectors, including hospitality and cultural promotion. This research contributes valuable insights into the multifaceted aspects of the carving industry in Thailand, encompassing educational structures, career trajectories, technical intricacies, and diverse applications within this artistic craft.